Raves, drugs,dealing and driving:qualitative data from a Western Australian sample - Lenton, Simon; Davidson, P. (1999)
This qualitative paper from a study of 83 people who attended raves or dance parties in Perth, Western Australia describes what respondents saw as the attractions and less good things about the rave/dance party scene, their views of the place of drug use within the scene, experiences obtaining and providing drugs and addresses the issue of driving while intoxicated. Non-drug factors such as lighting, music, dancing, the non-violent atmosphere,sense of social cohesion and relative lack of predatory male sexual behaviour were the major attractions of the scene,yet it was noted that these were enhanced by the effects of dance drugs,especially ecstasy. There were dual concerns that younger participants were at increased risk of drug-related harm and brought unwanted drug-related media attention and disrepute on the scene. The study supports the view that raves are not "drug supermarkets",with most respondents obtaining their drugs many days before the event. A substantial minority of respondents described travelling to or from raves with drivers who were drug-affected. Less than half of those who discussed the issue said they considered whether the driver was under the influence. This is of concern and has implications for policing practices, peer education and race-related materials.